Numerical methods with MATLAB : a resource for scientists and engineers - Borse, Garold J. (PWS, 1997)
Linear analysis and matrices. MATLAB applied to functions of a single variable. Functions of two or more variables. Data analysis and modeling. Differential equations. Programming in MATLAB.